Role of C‐Defective Sites in CO Adsorption over ϵ‐Fe2C and η‐Fe2C Fischer‐Tropsch Catalysts. Issue 23 (4th November 2020) - Cao, Junbo; Song, Nan; Chen, Wenyao; Cao, Yueqiang; Qian, Gang; Duan, Xuezhi; Zhou, Xinggui
Abstract: Herein, we report the crucial importance of C‐defective sites on the CO adsorption over ϵ‐Fe2 C and η‐Fe2 C Fischer‐Tropsch catalysts via systematic DFT calculations. The simulated XRD and Wulff construction show the significant differences in their equilibrium shapes and most exposed surfaces. It is observed that the ϵ‐Fe2 C exposes a high proportion (89 %) of facets (1 2 ‾ 1) with similar structure to that of η‐Fe2 C (011) which has been proved to be the active surface of CO activation. Abstract : Crucial importance of C‐defective sites on the CO adsorption over ϵ‐Fe2 C and η‐Fe2 C Fischer‐Tropsch catalysts via systematic DFT calculations has been disclosed. The simulated XRD and Wulff construction show significant differences in their equilibrium shapes and most exposed surfaces.